The horse in my garage and other stories ebook - McManus, Patrick F. (2019)
A collection of sidesplitting humor about the great outdoors from the author of A Fine and Pleasant Misery . In The Horse in My Garage and Other Stories, humorist Patrick F. McManus's best and funniest anecdotes on flora, fauna, and getting on Mother Nature's last nerve are proudly on display. Read about the antics of Patrick's friends Rancid Crabtree and Retch Sweeney in such stories as "Shaping Up for the Hunt" and "Bear Hunters." McManus plays off the recent obsession with hoarders in his surprising story "The Lady Who Kept Things." And in the title story, you'll meet Patrick's horse, Huckleberry, and learn of all the problems that come along with owning your own horse—and keeping him in the garage. Other stories include: "Catch-and-Eaters," about the importance of a forked stick when fishing. "$7000 TV Historical Extravaganza," a look at one director's loose interpretation of historical accuracy and political correctness. "A Lake Too Far," concerning the woes of Patrick and his wife, Bun, on a fateful birding trip in Australia. "Chicken Chronicles," which involves Patrick's memory of wandering around naked in the chicken yard when guests came to call. (Don't ask!) So pull up a chair, sit back, and enjoy the adventures of Patrick F. McManus as only he can tell them. "Everybody should read Patrick McManus." — The New York Times Book Review